Book Building vs Fixed Price Revisited: The Case of Indonesia - Tri Utami; Arief Surya Irawan (Universitas Muhammadiyah Surakarta, 2022)
We revisited the evidence on how IPO methods affect return (opening, close and initial return) and why does return affects the volatility in Indonesia. As one of the emerging countries, Indonesia had a changing regulation regarding the IPO method from the fixed price to the book building method since October 2000. Using a clustering regression analysis method, we find that the opening price and initial price in the book building period are significantly higher than that in the fixed price period. Furthermore, there is no effect of the opening return on the volatility. In contrast, closing return affects the volatility positively, while the relationship between initial return and volatility shows somewhat mixed results.